Odpowiedzi

  • Użytkownik Zadane
2009-12-07T15:59:16+01:00
A)(2t+1)(1-3t)= 2t-6t2+1-3t= -4t2-3t+1

b)(3ab-7)(3-7ab)= 9ab-21a2b2-21+49ab= 58ab-21a2b2

c)(-x+y)(5x+6y)=-5x-6y+5xy+6y2

d)(x+5y)(7x-y)= 7x2-xy+35y-5y2


e)(2x⁴-y)(x⁴+y)= 2x16+2x4y-x4y-y2= 2x16 +x4y-y2



f)(ab-a)(2ab+6a)= 2a2b2+6a2b-2a2b-6a2
Najlepsza Odpowiedź!
2009-12-07T16:09:41+01:00
A) (2t+1)(1-3t)=
2t-6t²+1-3t
-t-6t²+1
b) (3ab-7)(3-7ab)
9ab-21ab²-21+49ab
58ab-21ab²-21
c) (-x+y)(5x+6y)
-5x²-6xy+5xy+6y²
-5x²-xy+6y²
d)(x+5y)(7x-y)
7x²-xy+35xy-5y²
7x²+34xy-5y²
e)(2x⁴-y)(x⁴+y)
2x⁸-2yx⁴-yx⁴-y²
2x⁸-3yx⁴-y²
f)(ab-a)(2ab+6a)
2ab²+6a²b-2a²b-6a₂
2ab²+4a²b-6a²